Die lewe en werk van Philipp Melanchthon (1497–1560): "n Leksikografiese bydrae tot Reformasie 500 - Wyk, Ignatius W. C.Van (HTS teologiese studies, 2017)
This article is a contribution to a research project of the Department of Church History and Church Polity at the University of Pretoria on the biography and work of the Reformers of the sixteenth century and their followers. The life and work of Philipp Melanchthon receives attention in the article. Melanchthon’s contribution to Reformation theology as well as his contributions to church-life, are described. Melanchthon was the man next to Luther and he therefore has to receive attention in this year of celebration and commemoration.